Structural and cyclical effects of tax progression - Jana Kremer; Nikolai Stähler (Deutsche Bundesbank, 2013)
In a real business cycle model with labor market frictions, we find that a more progressive tax schedule reduces structural unemployment as it fosters long-run incentives for job creation. Because there exists an optimal level of unemployment in a matching environment ('Hosios condition'), tax progression improves steadystate welfare up to a certain threshold and harms it beyond that. However, tax progression increases the costs of business cycles for those consumers who can save and borrow, while it reduces the business cycle costs for households with limited asset market participation ('rule-of-thumb' consumers). Our analysis suggests that business cycle effects dominate steady-state effects. On the aggregate level, tax progression is welfare-enhancing up to a certain threshold and always shifts relative utility from optimizing to rule-of-thumb consumers. These findings are quite robust to alternative calibrations of our model.
Keywords: H2; J6; E32; E62; 330; Tax Progression; Business Cycles; Automatic Stabilizers; Welfare